IOS 12 programming for beginners : an introductory guide to IOS app development with Swift 4. 2 and Xcode 10 - Clayton, Craig (Packt Publishing Ltd, 2018)
This book guides you through every aspect of iOS development. From Xcode and Swift, the building blocks of modern iOS development, you'll quickly gain a solid foundation to begin venturing deeper into your development journey.